Funções executivas: avaliação informatizada em crianças bilíngues - Barbam, Aline (2020)
Bilingualism is a worldwide phenomenon that has increased in Brazil. Research suggests that there are advantages for bilingual individuals when compared to monolinguals in tasks that measure executive functions, such as inhibitory control, working memory and cognitive flexibility. One explanation found in the literature is that this advantage appears to bilinguals because of the frequent use of two language codes. This daily practice leads the bilingual to inhibit the language that is not being used with a particular interlocutor, thus obtaining a practice in inhibitory control, which seems to contribute to the development of executive functions. However, the literature results are not consensual and there are few studies with Brazilian children. In this context, the present study aimed to analyze the development of executive functions along the preschool and the first year of elementary, and to analyze the relation of the EF to the language tests applied in Portuguese and English in order to verify if children with better performances (and therefore in a higher level of bilingualism) also presented better performances in the EF. The research was conducted with 65 students of bilingual schools located in São Paulo, with children from 4 to 7 years old. All students were Portuguese speakers that were exposed to English at school in an immersion educational method. English and Portuguese tests were used to evaluate the language as: Teste Infantil de Nomeação – versão reduzida (TIN-vr) and Teste de Vocabulário por Imagens Peabody (TVIP). Two other instruments were used to evaluate the executive functions: the Computerized Evaluation of Executive Functions (TAFE); and the Inventário de Dificuldades em Funções Executivas, Regulação e Aversão ao Adiamento para crianças e adolescentes (IFERA-I) filled in by teachers and parents. The results corroborate the theoretical assumptions about the grade effects of the executive functions on children in early childhood education and early elementary school, revealing that more advanced grades perform better than early grades. However, the number of significant correlations between the language tests and the executive functions tests was modest, and the results were not consistent, so some correlations pointed out advantages of bilingual children, while others pointed out the opposite. A moderate magnitude correlation was observed among the tests scores and the answers given by parents and teachers in the IFERA-I for the working memory and inhibitory control constructs. Such results can be studied more deeply in future research with children of other ages. In general, the Executive Functions instruments showed correlations with each other and progression throughout the series, however there was a relation with the proficiency level in Portuguese and English, which may suggest that, on this sample of bilingual children exposed to English in school immersion context, the proficiency on both languages doesn’t relate in an evident way to the Executive Functions